Lizardite “kolskite” from the Lesnaya Varaka alkaline ultrabasic massif (Kola peninsula): new data - M. O. Bulakh (Известия высших учебных заведений: Геология и разведка)
Background. A rare morphological variety of magnesian serpentine, described in 1939 in the veins of the Lesnaya Varaka alkaline ultrabasic massif (Kola Peninsula) under the name “kolskite” is studied. For a long time, this variety has been considered an antigorite.Aim. Identification of the polymorphic modification of “worm-like” serpentine; determination of its crystal chemical features and possible genesis.Materials and methods. Samples were studied using electron probe analysis and scanning electron microscopy by a Jeol JSM-IT500 scanning electron microscope equipped with an INCA X-Max energy dispersion spectrometer; powder X-ray diffraction; infrared spectroscopy using a FSM-1201 IR Fourier spectrometer; and Raman spectroscopy using a EnSpectr R532 spectrometer.Results. Serpentine “kolskite” is represented by lizardite with the empirical formula (Mg2.79Al0.04Fe3+0.01)∑2.84[Si2.06O5](OH)4. The calculated parameters of the trigonal unit cell are as follows: a = 5.32(1) Å, c = 7.88(2) Å, V = 193.0(1) Å3. An increase in parameter c compared to that of apoolivine lizardite typical of ultrabasic objects indicates an expansion of the interlayer distance and is associated with serpentine hydration.Conclusion. The formation of “worm-like” lizardite aggregates could occur either by replacing vermiculite under the action of low-temperature alkaline hydrothermal solutions, or as a result of hypergenic alteration in the earlier apoolivine serpentine.